2015
DOI: 10.1021/acs.biochem.5b00663
|View full text |Cite
|
Sign up to set email alerts
|

SufE D74R Substitution Alters Active Site Loop Dynamics To Further Enhance SufE Interaction with the SufS Cysteine Desulfurase

Abstract: Many essential metalloproteins require iron–sulfur (Fe–S) cluster cofactors for their function. In vivo persulfide formation from L-cysteine is a key step in the biogenesis of Fe–S clusters in most organisms. In Escherichia coli, the SufS cysteine desulfurase mobilizes persulfide from L-cysteine via a PLP-dependent ping-pong reaction. SufS requires the SufE partner protein to transfer the persulfide to the SufB Fe–S cluster scaffold. Without SufE, the SufS enzyme fails to efficiently turn over and remains lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…These included peptides covering active site residues, 225–236 and 356–366, and peptides covering the dimer interface, 88–100 and 243–255 (Figure 6A). Changes in the two active site regions had previously been identified by HDX-MS when SufE or an activated variant of SufE (D74R SufE) bound to SufS 14, 15 . HDX-MS results with the activated D74R SufE also indicated changes in peptide 88–100, suggesting that the dimer interface is sensitive to activated intermediates in the SufS/SufE reaction.…”
Section: Discussionmentioning
confidence: 99%
“…These included peptides covering active site residues, 225–236 and 356–366, and peptides covering the dimer interface, 88–100 and 243–255 (Figure 6A). Changes in the two active site regions had previously been identified by HDX-MS when SufE or an activated variant of SufE (D74R SufE) bound to SufS 14, 15 . HDX-MS results with the activated D74R SufE also indicated changes in peptide 88–100, suggesting that the dimer interface is sensitive to activated intermediates in the SufS/SufE reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of SufE greatly enhances SufS activity up to 200-fold over SufS alone. Previous studies have suggested that SufE also influences the SufS activesite allosterically and could impact specific steps in the cysteine desulfurase reaction as well (37,38).…”
Section: A Detailed Mechanism For Sufsmentioning
confidence: 99%
“…Examination of the structure of the resting SufE shows a variety of interactions that hold the active site loop folded down into the interior of SufE and reveals that the Asp74 residue would play a key role for maintaining such a structure. Amide hydrogen/deuterium exchange mass spectrometry (HDX-MS) analysis of the SufE D74R mutant revealed an increase in solvent accessibility and dynamics in the loop containing the active site Cys51 used to accept persulfide from SufS [77]. In addition, SufE D74R mutant is a better sulfur acceptor for SufS than wt SufE.…”
Section: Structural and Biophysical Analyses Of Suf Proteinsmentioning
confidence: 99%
“…This induces a SufE conformational change by making the Cys51 active site loop more dynamic. In addition, it was shown that this mutation promotes higher interaction of SufE with SufS [77]. Therefore, this mutation enhances the ability of SufE to accept sulfur from SufS.…”
Section: Structural and Biophysical Analyses Of Suf Proteinsmentioning
confidence: 99%